Consider the eye in preventive healthcare – ocular findings, intraocular pressure and Schirmer tear test in ageing cats. Issue 12 (December 2018) - Sandhas, Ellen; Merle, Roswitha; Eule, J Corinna
Objectives: Geriatric health screening in cats is highly recommended. However, information about normal and abnormal findings is scarce, especially regarding the eyes of ageing cats. This prospective study examined the influence of the ageing process on vision and ocular structures in older cats. Methods: A total of 209 cats (aged 9–24 years) underwent physical examination, vision assessment, slit lamp biomicroscopy and ophthalmoscopy. Systolic blood pressure (SBP) measurement, Schirmer tear test (STT) reading and rebound tonometry were performed. Systemic disease was not a criterion for exclusion. Results: Vision was good in 157/209 cats (75.1%) and impaired in 52/209 cats (24.9%). Increasing age and the occurrence of vision impairment were not statistically associated ( P = 0.053). Retinal oedema, retinal haemorrhage and/or retinal detachment (19 cats) and glaucoma (12 cats) were the most common findings in vision impaired cats. Increasing age was significantly associated with the occurrence of lenticular sclerosis ( P = 0.01) and attenuated retinal vessels ( P = 0.02). Increasing age and SBP were significantly associated with the occurrence of retinal detachment, haemorrhage and oedema ( P <0.001 each). In cats without evidence of hypertensive ocular damage, younger cats had a tendency for higher SBP values than older cats, although this difference was not significant. Mean intraocular pressure (IOP) was 16.5 ± 5.0 mmHg. Age did not significantly affect the IOP values ( P = 0.54). Mean STT was 15.8 ± 4.8 mm/min. The STT was found to increase with age ( P = 0.025). Conclusions and relevance: Although vision impairment is not a clinical sign of old age in cats, age-related changes may contribute to vision-threatening diseases. This study contributes to preventive healthcare by examining the influence of the ageing process on vision and ocular structures in older cats.